A new era in electroencephalographic monitoring? Subscalp devices for ultra–long‐term recordings. (27th August 2020) - Duun‐Henriksen, Jonas; Baud, Maxime; Richardson, Mark P.; Cook, Mark; Kouvas, George; Heasman, John M.; Friedman, Daniel; Peltola, Jukka; Zibrandtsen, Ivan C.; Kjaer, Troels W.
Abstract: Inaccurate subjective seizure counting poses treatment and diagnostic challenges and thus suboptimal quality in epilepsy management. The limitations of existing hospital‐ and home‐based monitoring solutions are motivating the development of minimally invasive, subscalp, implantable electroencephalography (EEG) systems with accompanying cloud‐based software. This new generation of ultra–long‐term brain monitoring systems is setting expectations for a sea change in the field of clinical epilepsy. From definitive diagnoses and reliable seizure logs to treatment optimization and presurgical seizure foci localization, the clinical need for continuous monitoring of brain electrophysiological activity in epilepsy patients is evident. This paper presents the converging solutions developed independently by researchers and organizations working at the forefront of next generation EEG monitoring. The immediate value of these devices is discussed as well as the potential drivers and hurdles to adoption. Additionally, this paper discusses what the expected value of ultra–long‐term EEG data might be in the future with respect to alarms for especially focal seizures, seizure forecasting, and treatment personalization.